"Factory-like" horizontal well plan optimization techniques in tight oil exploration—A case study in Fuyu oil-bearing layer of Y63 well block, Northern Songliao Basin. Issue 1 (August 2021) - Sun, Hailei; Zhu, Zhengyuan
Abstract: In Zhaoyuan region of Sanzhao Depression, Fuyu oil layer is of considerable resource potential, and its tight reservoir is continuous and extensively oil-bearing. How to improve the deliverability of tight reservoir, however, is still a major problem facing explorationists. As for the sweet spot Y63 in Zhaoyuan region, this paper uses well logging, well testing and laboratory test data to identify the geological characteristics of F II 1, determines the sand body boundaries of the sweet spot by means of seismic attributes and geostatistical inversion, and then carry out batches of horizontal well plans on the same platform. The drilling result of five horizontal wells shows that the oil layer thickness ranges from 934m to 1177m, with an average of 1080m. By comparison with its adjacent straight wells, the deliverability of horizontal well is improved by a factor of 5-12. This proves the advantage and feasibility of the horizontal well plan proposed in this paper.